Estratégias contemporâneas para o desenvolvimento de competências-chave na educação infantil - Kanarova, Olha; Butenko, Vita; Frolenkova, Nadiia; Pisotska, Leonida; Sas, Olena (Revista on line de Política e Gestão Educacional, 2025)
The article evaluates the effectiveness of modern methodological approaches in developing key competencies in early childhood education. Methods included literature analysis, the study of pedagogical innovations, questionnaires with parents and educators, and experimental research. The competencies addressed include health, communication, language, social relationships, personal development, cognitive, play-based, and environmental aspects. The study proposes pedagogical strategies categorized into traditional and innovative approaches, with emphasis on contemporary methodologies such as STEAM integration, use of sensory zones, and mindfulness techniques.